UPAYA MENINGKATKAN AKTIVITAS SISWA DALAM MATERI ATURAN SINUS DAN COSINUS MELALUI METODE INQUIRY DI KELAS X IPA.1 SMA NEGERI 1 MUARO JAMBI - S Waltuti (Universitas Batanghari Jambi, 2018)
Abstract: The aim of this research is to find out how the inquiry method can improve the students learning outcomes about mathematical theories. The method of this research was classroom action research. The implementation of this research used two cycles, in which each cycle consisted of two meetings. The data used in this research were field notes and observation format. The data analysis used a percentage system in order to see the students’ activity, specifically for the topic of the lesson sine and cosine. Processing of learning results used statistical theory by finding the average value, absorption and minimum criteria at the end of the cycle. The results showed that the inquiry method can improve the students learning outcomes in the learning process. It was indicated by the significant improvement of students’s score from 53.12% to 70.83%.The average of student learning outcomes of cycles I and II were 58.91 and 75.78.The completeness of student learning outcomes increased from 53, 12% to 87.50 %.Keywords: Students’ Activity, Rules of Sine and Cosine, Inquiry Method